ASSOCIATION BETWEEN MICROALBUMINURIA AND OXIDATIVE STRESS IN DIABETIC NEPHROPATHY - Rao, P Prabhakar; Sujatha, C; Madhavi Latha, N; Kumar, J Praveen; Deepa, M (International Journal of Clinical and Biomedical Research, 2015)
Objectives: Diabetic Nephropathy (DN) is a leading cause of chronic kidney disease and end stage renal failure worldwide. This study aimed to evaluate the association between oxidants, antioxidants and microalbuminuria in Diabetic Nephropathy compared with Type II Diabetes Mellitus (DM). Methods: The study includes 60 Type II Diabetes Mellitus and 40 Diabetic Nephropathy Patients. Parameters performed HbA1c, urea, creatinine, total proteins, microalbuminuria, glutathione peroxidase and malondialdehyde(MDA). Results: The levels of HbA1c, urea, creatinine, microalbuminuria and malondialdehyde are significantly higher in DN compared with Type II DM. the levels of T.P and glutathione peroxidase are decreased in DN compared with Type II DM. Conclusion: Low levels of glutathione peroxidase and total proteins were observed in DN. HbA1c, urea, creatinine, microalbuminuria and malondialdehyde levels were elevated in DN compared with Type II DM. KEYWORDS: Diabetic Nephropathy; Glutathione peroxidase; Microalbuminuria; Malondialdehyde.